MRI-Derived Restriction Spectrum Imaging Cellularity Index is Associated with High Grade Prostate Cancer on Radical Prostatectomy Specimens - Liss, Michael A.; White, Nathan S.; Parsons, J. Kellogg; Schenker-Ahmed, Natalie M.; Rakow-Penner, Rebecca; Kuperman, Joshua M.; Bartsch, Hauke; Choi, Hyung W.; Mattrey, Robert F.; Bradley, William G.; Shabaik, Ahmed; Huang, Jiaoti; et al. (Frontiers in Oncology, 2015)
Objectives: We evaluate a novel magnetic resonance imaging (MRI) technique to improve detection of aggressive prostate cancer. Methods: We performed a retrospective analysis of presurgical prostate MRI scans using an advanced diffusion weighted imaging technique called Restriction Spectrum Imaging (RSI), which can be presented as a normalized z-score statistic (RSI z-score). Scans were acquired prior to radical prostatectomy. Prostatectomy specimens were processed using whole mount sectioning and regions of interest (ROIs) were drawn around individual prostate cancer (PCa) tumors. Corresponding ROIs were drawn on the MRI imaging and paired with ROIs in regions with no pathology. RSI z-score and conventional apparent diffusion coefficient (ADC) values were recorded for each ROI. Paired t-test, ANOVA and logistic regression analyses were performed. Results: We evaluated 28 patients with 64 regions of interest (28 benign and 36 PCa). The mean difference in RSI z-score (PCa ROI – Benign ROI) was 2.17 (SE = 0.11; p <0.001) and in ADC was 551 mm2/sec (SE = 80 mm2/sec; paired t-test, p <0.001). The differences in the means among all groups (benign, primary Gleason 3 and primary Gleason 4) was significant for both RSI z-score (F3,64 = 97.7, p <0.001) and ADC (F3,64 = 13.9, p <0.001). A t-test was performed on only PCa tumor ROIs (n=36) to determine prostate cancer aggressiveness (Gleason 3 vs. Gleason 4) revealing that RSI z-score was still significant (p = 0.03), whereas, ADC values were no longer significant (p = 0.08). In multivariable analysis adjusting for age and race, RSI z-score was associated with PCa aggressiveness (OR 10.3, 95%CI: 1.4-78.0, p=0.02) while ADC trended to significance (p=0.07). Conclusions: The RSI derived normalized cellularity index (RSI z-score) is associated with aggressive prostate cancer as determined by pathologic Gleason scores. Further utilization of RSI techniques may serve to enhance standardized reporting systems.